Clinical and genetic correlates of mitral valve pathology in patients with heritable thoracic aortic disease: results from the montalcino aortic consortium. (3rd October 2022) - De Backer, J; Renders, W; Braverman, A; Jeremy, R; Jondeau, G; Prakash, S; Teixido Tura, G; Shalhub, S; Yetman, A; Milewicz, D; Muino Mosquera, L
Abstract: Background: Mitral valve (MV) pathology, including prolapse and regurgitation, is a well-known cardiovascular manifestation associated with the genes that predispose to Heritable Thoracic Aortic Disease (HTAD). The extent to which there are differences in prevalence, presentation and severity of MV pathology as a function of the underlying genetic cause has not been investigated in detail. Purpose: Assess the prevalence, presenting features and outcome of mitral valve pathology according to the underlying genetic defect in patients with HTAD. Study design: We leveraged clinical and genetic data of a large international multicenter retrospective cohort study. Probands and relatives with a validated (likely) pathogenic (LP/P) variant in 8 HTAD genes were included. Genes were categorized in 2 groups: Group 1 encoding for components of the TGFβ pathway (TGFBR1, TGFBR2, SMAD3 and TGFB2) and Group 2 encoding for proteins involved in vascular smooth muscle cell contraction (VSMC) (ACTA2, MYLK, PRKG1, MYH11). Comparison between these groups was performed. MV pathology was defined as at least moderate MV regurgitation, MV prolapse and past MV surgeries. Results: A total of 459 patients. 68.8% of the patients carried a variant in one of the Group 1 genes and 31.2% had a Group 2 gene variant. 52 patients (11.3%) presented MV pathology. Significant differences in MV status according to the gene group were present: 15.5% of the patients in group 1 presented MV disease, versus 2.1% in group 2, (p<0.001). Within Group 1, LP/P variants in SMAD3 were most common (32.7%), followed by TGFBR2 (25.0%) and TGFB2 (23.1%) (p=0.006). The remaining 5.8% of MV pathology cases were patients carrying ACTA2 variants. No MV pathology was found in MYLK, PRKG1 and MYH11 variant carriers. Compared to patients without MV pathology, patients with MV pathology more often underwent aortic aneurysm repair (34.6% vs 15.5%, p<0.001). To the contrary, aortic dissection/rupture occurred less frequently in patients with MV pathology (7.7% vs 26.8%, p<0.001). No differences were observed for prevalence of congenital heart defects, left ventricular dilatation, arrhythmic events or heart failure. Conclusion: Patients with HTAD carrying LP/P variants in genes encoding TGFβ components present more frequently with MV pathology than patients carrying variants in genes encoding proteins involved in VSMC contraction. In the latter group, only patients carrying ACTA2 variants presented MV pathology. Patients with MV pathology are more likely to undergo aortic aneurysm repair and present less frequently with aortic dissection/rupture. Whether the presence of MV pathology accelerates the diagnosis and hence leads to a more aggressive management/stricter surveillance in these patients and/or whether biological differences between these genetic entities explain these differences requires further study. These data provide tools for developing improved, gene-tailored management of patients with HTAD. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Baillet Latour FoundationFunds for Scientific Research Flanders